Yttrium complexation and hydration in chloride-rich hydrothermal fluids: A combined ab initio molecular dynamics and in situ X-ray absorption spectroscopy study. (15th July 2020) - Guan, Qiushi; Mei, Yuan; Etschmann, Barbara; Testemale, Denis; Louvel, Marion; Brugger, Joël
Abstract: Accurate knowledge of rare earth elements (REE) speciation in high pressure – high temperature fluids is required to model REE transport and precipitation in subduction zones and magmatic-hydrothermal environments, and the formation of rare metal deposits. Recent experiments (lanthanum, ytterbium, erbium) have demonstrated that REE chloride complexes are the main REE form in many hydrothermal fluids (Migdisov et al., 2016). However, the speciation of yttrium (Y(III)), a cation with an ionic radius similar to that of Ho(III), remains poorly constrained in chloride-rich hydrothermal solutions. We used ab initio molecular dynamics (MD) simulations to calculate the nature of Y(III)-Cl complexes and the thermodynamic properties of these species at temperatures up to 500 °C and pressures of 800 bar and 1000 bar. The MD results were complemented by in situ X-ray absorption spectroscopy (XAS) measurements. Our results indicate that at temperatures below 200 °C, chloro-complexes do not form readily, even in highly concentrated brines. At ambient condition, the Y(III) aqua ion binds to eight water molecules in a square antiprism geometry, which is consistent with previous ab initio studies (Ikeda et al., 2005a). The thermodynamic integration method was employed to calculate the formation constants (log K Θ ) of Y(III)-Cl − complexes in two simulation boxes containing different Y:Cl ratios; we obtained very consistent results of the standard log K Θ of the individual complexes from the two independent calculations, which confirms that the thermodynamic integration method is reliable and not significantly affected by technical limitations in box size, box composition, or simulation time. Based on the derived formation constants, we fit modified Ryzhenko–Bryzgalin (MRB) equation of state parameters, which enable extrapolation of the formation constants at elevated temperature and pressure. The results are consistent with the XAS data, and show that the stability of Y(III)-Cl complexes increases with increasing temperature, Y(III) forming high order Cl − complexes (up to YCl4 − ) in high salinity solutions at high temperature and pH = 3. We also compare the extrapolated log K Θ with the available data for other REE at 150 °C, 200 °C and 250 °C. At 200 °C, yttrium behaves more like a heavy REE, but from 200 °C to 250 °C, the formation constants of Y(III)-Cl complexes increase dramatically and behave more like the light REE. The difference of Cl − dominant species between Ho(III) (HoCl 2+ ) and Y(III) (YCl2 + ) may account for the formation of anomalous Y/Ho ratios in some hydrothermal environments.